TOLANGO VILLAGE 1994-2011 - Rauf, Awalludin; Mohamad, Sutrisno; Manay, Helman (CV. Fahr Publishing, 2025)
This study aims to determine; First, the beginning of the formation of Tolango Village in 1994. Second, the development of Tolango Village from 1994-2011, both in the economic sector, education, and the development of village infrastructure in the period from 1994 to 2011. The method used in this study is Historical research with four stages of research, the first heuristic (collection of sources), source criticism (verification of sources) which in its scope is external and internal criticism, interpretation (interpretation), and the last is Historiography (writing history). The results of this study can be concluded that the formation of Tolango Village, namely in 1994, the formation of Tolango Village due to several factors. First, access distance, area, and a sense of competition between communities in different hamlets. The development of Tolango Village has begun to be felt by the people of Tolango Village. Second, significant developments can be seen from several aspects, such as in the economic sector, the use of agricultural land by the people of Tolango Village which has an impact on increasing the economy of the people of Tolango Village. Then in the field of education, namely the availability of fairly complete educational facilities. Furthermore, in the development of infrastructure, the availability of adequate infrastructure will certainly improve the welfare of the community.